The Effect of Zero Copayments on Medication Adherence in a Community Pharmacy Setting - Melissa Jimenez; Goar Alvarez; Albert Wertheimer; Leanne Lai; Leroy Koh; Dainelys Martinez; Bushra Hijazi; Mark Weinstein (University of Minnesota Libraries Publishing, 2019)
Background: Prescription medication copayments can be a financial burden to many patients. When patients cannot afford their medications, they may become nonadherent, and as a result, this can lead to an increase in chronic disease complications and healthcare costs. Objective: The objective of this study was to determine if zero copayments have an effect on medication adherence in a community pharmacy. Methods: This retrospective cohort study examined the prescription refill records of patients who filled specific generic medications for hypertension, hyperlipidemia, and gastroesophageal reflux disease (GERD) in 2016 at the NSU Clinic Pharmacy. The adherence rates of patients with zero copayments were compared to the adherence rates of patients with copayments greater than $0. Adherence was determined by calculating the proportion of days covered (PDC). Patients were considered adherent if their PDC was greater than or equal to 80%. Results: GERD patients with no copayments had average PDC ratios of 87.4% and were statistically significantly more adherent than GERD patients with copayments, who had average PDC ratios of 76.7% (P = 0.042). Hyperlipidemia and hypertension patients with no copayments had average PDC ratios of 89.3% and 90.3%, respectively, and those with copayments had PDC ratios of 85.3% (P = 0.314) and 87.9% (P = 0.534). Conclusion: Overall, patients with $0 copayments had higher adherence rates than patients with copayments greater than $0. GERD patients with no copayments were significantly more adherent than GERD patients with copayments. However, no statistically significant difference was found between patients with or without copayments in the hyperlipidemia and hypertension cohorts. Further studies are recommended to analyze additional factors that may influence medication adherence.   Article Type: Original Research